Relugolix Combination Therapy for Uterine Leiomyoma–Associated Pain in the LIBERTY Randomized Trials. Issue 6 (2nd June 2022) - Stewart, Elizabeth A.; Lukes, Andrea S.; Venturella, Roberta; Arjona Ferreira, Juan-Camilo; Li, Yulan; Hunsche, Elke; Wagman, Rachel B.; Al-Hendy, Ayman
Abstract : In women with heavy menstrual bleeding associated with uterine leiomyomas, once-daily relugolix combination therapy significantly improved uterine leiomyoma–associated pain during both menstrual and nonmenstrual days. Abstract : OBJECTIVE: To assess the effect of once-daily relugolix combination therapy (relugolix-CT: relugolix 40 mg, estradiol 1 mg, and norethindrone acetate 0.5 mg) compared with placebo on moderate-to-severe pain in women with uterine leiomyomas and heavy menstrual bleeding. METHODS: Two replicate, multinational, double-blind, 24-week, randomized, phase 3 studies (LIBERTY 1 and 2) were conducted in premenopausal women with uterine leiomyoma–associated heavy menstrual bleeding (80 mL or greater per cycle for two cycles or 160 mL or greater during one cycle). A predefined secondary objective was to determine the effect of relugolix-CT on moderate-to-severe uterine leiomyoma–associated pain in the pain subpopulation (women with maximum pain scores of 4 or higher on the 0–10 numerical rating scale at baseline, with pain score reporting compliance of 80% (ie, 28 days or more over the last 35 days of treatment). This key secondary endpoint was defined as the proportion of women achieving minimal-to-no uterine leiomyoma–associated pain (maximum numerical rating scale score 1 or lower) at week 24; menstrual and nonmenstrual pain were evaluated in prespecified secondary analyses. Treatment comparisons were performed in the pooled LIBERTY 1 and 2 pain subpopulation using the Cochran-Mantel-Haenszel test stratified by baseline menstrual blood loss volume. RESULTS: Across both trials, 509 women were randomized to relugolix-CT or placebo (April 2017–December 2018). Of these, 277 (54.4%) met pain subpopulation requirements. With relugolix-CT, 45.2% (95% CI 36.4–54.3) of women achieved minimal-to-no pain compared with 13.9% (95% CI 8.8–20.5) with placebo (nominal P <.001). The proportions of women with minimal-to-no pain during menstrual days and during nonmenstrual days were significantly higher with relugolix-CT (65.0% [95% CI 55.6–73.5] and 44.6% [95% CI 32.3–57.5], respectively) compared with placebo (19.3% [95% CI 13.2–26.7], nominal P <.001, and 21.6% [95% CI 12.9–32.7], nominal P =.004, respectively). CONCLUSION: Over 24 weeks, relugolix-CT significantly reduced moderate-to-severe uterine leiomyoma–associated pain with a more pronounced effect on menstrual pain. These data support that relugolix-CT had clinically meaningful effects on women's experience of uterine leiomyoma–associated pain. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov: LIBERTY 1, NCT03049735; LIBERTY 2, NCT03103087. FUNDING SOURCE: Myovant Sciences GmbH.